The advantages, pitfalls and limitations of guideline‐directed medical therapy in patients with valvular heart disease. (8th February 2021) - Gill, Harminder; Chehab, Omar; Allen, Christopher; Patterson, Tiffany; Redwood, Simon; Rajani, Ronak; Prendergast, Bernard
Abstract: Heart failure is an inevitable end‐stage consequence of significant valvular heart disease (VHD) that is left untreated and increasingly encountered in an ageing society. Recent advances in transcatheter procedures and improved outcomes after valve surgery mean that intervention can (and should) be considered in all patients – even the elderly and those with multiple comorbidities ‐ at earlier stages of the natural history of primary VHD, before the onset of irreversible left ventricular dysfunction (and frequently before the onset of symptoms). All patients with known VHD should be monitored carefully in the setting of a heart valve clinic and those who meet guideline criteria for surgical or transcatheter intervention referred for intervention without delay. High quality evidence for the use of medical therapy in VHD is limited and achieving target doses in an elderly and comorbid population frequently challenging. Furthermore, determining whether the valve or ventricle is the principal disease driver is crucial (although the distinction is not always binary, and often unclear). Guideline‐directed medical therapy remains the mainstay of treatment for secondary mitral regurgitation ‐ although up to 50% of patients may fail to respond and should be considered for cardiac resynchronization, transcatheter or surgical valve intervention. Early and definitive management strategies are essential and should be overseen by a specialist Heart Team that includes a Heart Failure specialist. In this article, we provide an evidence‐based summary of approaches to the medical treatment of VHD and clinical guidance for the best management of patients in situations where high quality evidence is lacking. Abstract : A schematic diagram summarising key principles of management in patients with heart failure and valvular heart disease.